A method to induce human cortical long-term potentiation by acoustic stimulation. (3rd October 2017) - Lei, Guanxiong; Zhao, Zeqi; Li, Yalan; Yu, Liming; Zhang, Xin; Yan, Yan; Ma, Xiaoyan; Wang, Qian; Wang, Keshuang; Zhang, Duo; Shen, Weidong; Qiao, Yuehua; et al.
Abstract: Object: Acoustic stimulation induced LTP in the human auditory cortex was successfully recorded for the first time by electroencephalography (EEG) using a stimulus of 1 kHz pure-tone in 2005. However, it was barely reproduced, given considerable challenges to reliably elicit and accurately record the enhanced potentials in vivo . The purpose of this paper was to explore whether acoustic stimuli other than 1 kHz pure-tone could generate LTP or not. Measures: To answer this question, we proposed a tetanic-stimulation paradigm of pure-tones, narrow-band noises (NBNs) and white noise (WN) to elicit LTP in human subjects. Results: The results showed that pure-tones with different frequency could elicit LTP in human auditory cortex, and proved for the first time that NBNs and WN could also achieve the same goal. Interestingly, it was also shown that the noises with certain bandwidth induced the greatest LTP and the WN induced LTP had the least variation over time and across subjects in comparison with pure-tones and NBNs. Conclusions: In light of the results, we suggested to use the paradigm for broader studies of human in vivo cortical plasticity.